The Influence of Profitability, Liquidity and Business Risk on Capital Structure - Amanda, Khania D; Suryanto, Wirawan (Indonesian Development of Economics and Administration Journal, 2024)
The purpose of this study is to analyze the effect of profitability, liquidity, and business risk on the capital structure of property and real estate sub-sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. Profitability is measured using Return on Assets (ROA), liquidity is measured using the Current Ratio (CR), business risk is measured using the Basic Earning Power Ratio (BEPR) and Capital Structure using Dept to Equity (DER). The method used in this study is quantitative with multiple linear regression analysis techniques to test the hypothesis. The results showed that ROA had a significant effect on DER, CR had an insignificant effect on DER, and BEPR had a significant effect on DER. Simultaneously, ROA, CR and BEPR had an effect on DER. The coefficient of determination obtained showed that the influence of ROA, CR and BEPR was 49.9% and the remaining 50.1% was influenced by other factors..